Penerapan Corporate Governance Sebagai Upaya Untuk Mengurangi Praktik Earnings Management di Perusahaan Go-Public - Widianingsih, Yuni Pristiwati N. (STIE Surakarta, 2012)
This study investigates the application of corporate governance to reduce earnings management on go-public firms.The results show that the proportion of independent commissioners has significant effect on earnings management; larger proportion of independent commissioners in the boards is associated with lower level of earnings management. Size of commissioners and leadership of independent commissioners have insignificant impact on earnings management. The proportion of independent director impacts significantly to the earnings management, larger proportion of independent director results on lower level of earnings management. Further size of director is positively associated with lower level of earnings management. Yet, audit committee is negatively associated with earnings management. This research provides evidences that effective board of commissioners, audit committee and board of directors are reducing earnings management.